Analisis Sebaran Lindi di Sekitar Kawasan TPA Batu Layang Berdasarkan Nilai Resistivitas: Analysis of Leachate Distribution Around Batu Layang TPA Area Based on Resistivity Value - Fitriana Meilasari; Hendri Sutrisno; Budhi Purwoko (BRIN Publishing (Penerbit BRIN), 2023)
Open dumping activities at the Batu Layang TPA can potentially cause leachate pollution to the environment. Leachate that seeps into the ground can contaminate groundwater. Most people around the Batu Layang TPA use groundwater for MCK (bath, wash, toilet) purposes. If the groundwater is contaminated with leachate and used sustainably by the community, it will impact health problems. Therefore, it is necessary to manage the distribution of leachate. One of the leachate management systems is modeling the potential distribution of leachate below the soil surface. The purpose of this research is to analyze the distribution of subsurface leachate around the Batu Layang landfill area based on the resistivity value. They are modeling the potential distribution of leachate below the ground surface in this study using the Wenner configuration geoelectric method. Processing of geoelectrical measurement data using Res2DInv software so that the potential distribution of leachate under the soil surface is obtained in 2 Dimensional forms. The result of this research is the resistivity value <10 m is interpreted as leachate, with an error rate (RMS error) of 7.7–11.3%. The geology of the study area is composed of peat soil, where the constituent rocks have high porosity (83.43–92.92%) and increased permeability (2.97×10-5–8.31×10-5 m/s). Porosity and permeability affect the infiltration of leachate into the soil. The topography of the study area is relatively flat, so it is estimated that the velocity of leachate distribution horizontally and vertically under the soil surface is moderate. ABSTRAK Kegiatan open dumping di TPA Batu Layang dapat berpotensi menyebabkan pencemaran lindi ke lingkungan. Lindi yang merembes ke dalam tanah dapat mencemari air tanah. Sebagian besar masyarakat di sekitar TPA Batu Layang memanfaatkan air tanah untuk keperluan MCK (mandi, cuci, kakus). Jika air tanah tersebut tercemar lindi dan dimanfaatkan secara berkesinambungan oleh masyarakat maka akan berdampak pada gangguan kesehatan. Oleh karena itu, perlu adanya pengelolaan sebaran lindi. Satu di antara sistem pengelolaan lindi adalah pemodelan potensi sebaran lindi di bawah permukaan tanah. Tujuan penelitian adalah analisis sebaran lindi bawah permukaan tanah di sekitar kawasan TPA Batu Layang berdasarkan nilai resistivitas. Pemodelan potensi sebaran lindi di bawah permukaan tanah pada penelitian ini menggunakan metode geolistrik konfigurasi Wenner. Pengolahan data hasil pengukuran geolistrik menggunakan software Res2DInv sehinggga didapatkan potensi sebaran lindi di bawah permukaan tanah dalam bentuk 2 Dimensi. Hasil dari penelitian ini adalah nilai resistivitas <10 Ωm diinterpretasi sebagai lindi, dengan tingkat kesalahan (error RMS) sebesar 7,7–11,3%. Geologi daerah penelitian tersusun oleh tanah gambut, dimana batuan penyusunnya memiliki porositas tinggi (83,43–92,92%) dan permeabilitas tinggi (2,97×10-5–8,31×10-5 m/s). Porositas dan permeabilitas mempengaruhi daya infiltrasi lindi ke dalam tanah. Topografi daerah penelitian relatif datar sehingga diperkirakan kecepatan sebaran lindi secara horizontal maupun vertikal di bawah permukaan tanah sedang.